Amdoparvoviruses in small mammals: expanding our understanding of parvovirus diversity, distribution, and pathology - Canuti, Marta; Whitney, Hugh G.; Lang, Andrew S. (Frontiers in Microbiology, 2015)
Many new viruses have been discovered recently, thanks in part to the advent of next-generation sequencing technologies. Among the Parvoviridae, three novel members of the genus Amdoparvovirus have been described in the last four years, expanding this genus that had contained a single species since its discovery, Aleutian mink disease virus. The increasing number of molecular and epidemiological studies on these viruses around the world also highlights the growing interest in this genus. Some aspects of amdoparvoviruses have been well characterized, however many other aspects still need to be elucidated and the most recent reviews on this topic are outdated. We provide here an up-to-date overview of what is known and what still needs to be investigated about these scientifically and clinically relevant animal viruses.